Pengembangan Karakter Perspektif Hidajat Nataatmadja : Dari Potensi Ke Aktualisasi - Qurun, Khoirotu Alkahfi (BINA' AL-UMMAH, 2020)
This article discusses the concept of developing humen character in Islamic perspective which reconstructed by an Indonesian scientist and intellectual, Hidayat Nataatmaja. As it is understood that character plays a very important role in forming one's attitudes and behavior, both as individuals,as a member of community and as a citizen of a nation as well, in order to achieve life goals that is in accordance with the right guidance (Islam). Character development becomes urgent, dealing with development of attitudes and behaviors that are contrary to both religious and cultural values (norms). Character development in Islamic perspective should be based on the value of monotheism (tauhid), based on Qur'an and Hadith texts and as they are in  thoughts of Islamic scholars and scientists, such as Hidajat Nataatmadja. The reconstruction of character formation aimed as an effort to prepare people, especially young muslim scientist who always have commitment to Islam as a true guidance.